Appendicitis as a cause of intestinal strangulation: a case report and review - Bhandari, Laxminarayan (BioMed Central, 2009)
Intestinal obstruction is a common surgical emergency caused by varied conditions. Appendicitis as a cause is both uncommon and unsuspected. Strangulation of intestine caused by appendicitis is extremely rare with very few cases reported in literature. The diagnosis of such a condition is possible only on table, with CT having questionable value. This is a very rare and dangerous complication of a very common disease which can easily be overlooked. Every emergency surgeon needs to be aware of such a possibility. We report a case of a 24 year old male presenting with classical features of intestinal obstruction. On laparotomy strangulated bowel was seen and appendix was found to be the cause. Although we obtained a history of appendicitis in this patient, it was not correlated to the present condition due to the rarity of such a scenario. We reviewed literature to find similar cases reported in the past.